2018
DOI: 10.1001/jamapediatrics.2017.4005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childhood Blood Lead Levels With Criminal Offending

Abstract: Importance Lead is a neurotoxin with well-documented effects on health. Research suggests lead may be associated with criminal behavior. This association is difficult to disentangle from low socioeconomic status, a factor in both lead exposure and offending. Objective To test the hypothesis that higher childhood blood-lead level (BLL) is associated with greater risk of (1) criminal conviction, (2) recidivism (repeat conviction), (3) violent conviction, and (4) variety of self-reported criminal offending, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…These studies document a positive correlation between lead exposure and various indicators of delinquency www.annualreviews.org • Environmental Inequality 271 (Amato et al 2013, Dietrich et al 2001, Reyes 2015a, Wright et al 2008. One recent study based on a 1972 birth cohort in Dunedin, New Zealand, with lead levels ranging from 4 to 31 µg/dL, reports that lead exposure in childhood, measured at age 11 years, had a weak relationship with official criminal convictions and self-reported offending from ages 15 to 38 years (Beckley et al 2018). 7 Four recent studies use different sources of exogenous variation in lead exposure to identify its effect on crime.…”
Section: Aggression and Crimementioning
confidence: 99%
“…These studies document a positive correlation between lead exposure and various indicators of delinquency www.annualreviews.org • Environmental Inequality 271 (Amato et al 2013, Dietrich et al 2001, Reyes 2015a, Wright et al 2008. One recent study based on a 1972 birth cohort in Dunedin, New Zealand, with lead levels ranging from 4 to 31 µg/dL, reports that lead exposure in childhood, measured at age 11 years, had a weak relationship with official criminal convictions and self-reported offending from ages 15 to 38 years (Beckley et al 2018). 7 Four recent studies use different sources of exogenous variation in lead exposure to identify its effect on crime.…”
Section: Aggression and Crimementioning
confidence: 99%
“…1 Elevated early-life exposure to inorganic lead had long-term consequences that much later were found to include psychopathies, delinquency and increased risk of cardiovascular disease in adulthood. [2][3][4] In the late 1950s, a Japanese fishing town was plagued by a mysterious illness that was at first thought to be infectious. Of note, a pregnant woman who ate seafood heavily contaminated with methylmercury might be unscathed herself but would give birth to a poisoned child with spastic paresis and intellectual disability.…”
Section: Lifelong Consequences Of Developmental Toxicitymentioning
confidence: 99%
“…Among these, the "silent epidemic" of lead exposure is a particularly well-replicated risk factor for violent and antisocial behavior (Glenn & Raine, 2014). More recent research, however, has observed only a weak association between high lead and antisocial behavior in New Zealand, where blood lead levels were not confounded with socioeconomic status (Beckley et al, 2018).…”
Section: Lead Exposurementioning
confidence: 99%